Discovery of three loci increasing resistance to charcoal rot caused by Macrophomina phaseolina in octoploid strawberry. Issue 3 (16th March 2021) - Nelson, Jonathan R; Verma, Sujeet; Bassil, Nahla V; Finn, Chad E; Hancock, James F; Cole, Glenn S; Knapp, Steven J; Whitaker, Vance M
Abstract: Charcoal rot caused by Macrophomina phaseolina is an increasing economic problem in annualized strawberry production systems around the world. Currently there are no effective postfumigation chemical controls for managing charcoal rot, and no information is available on the genetic architecture of resistance to M. phaseolina in strawberry ( Fragaria ×ananassa ). In this study, three multiparental discovery populations and two validation populations were inoculated at planting and evaluated for mortality in three consecutive growing seasons. Genome-wide SNP genotyping and pedigree-based analysis with FlexQTL™ software were performed. Two large-effect quantitative trait loci (QTL) increasing charcoal rot resistance were discovered and validated in cultivated germplasm. FaRMp1 was located on linkage group 2A in the interval 20.4to 24.9 cM, while FaRMp2 was located on linkage group 4B in the interval 41.1to 61.2 cM. Together these QTLs explained 27% and 17% of the phenotypic variance in two discovery populations consisting of elite breeding germplasm. For both QTLs, the resistant allele showed some evidence of partial dominance, but no significant interaction was detected between the two loci. As the dosage of resistant alleles increased from 0 to 4 across the two QTLs, mortality decreased regardless of the combination of alleles.A third locus, FaRMp3 on 4D, was discovered in FVC 11–58, a reconstituted F.×ananassa originating from diverse F. virginiana and F. chiloensis accessions. This locus accounted for 44% of phenotypic variation in four segregating crosses. These findings will form the basis for DNA-informed breeding for resistance to charcoal rot in cultivated strawberry.